CANDLE Syndrome As a Paradigm of Proteasome-Related Autoinflammation - Torrelo, Antonio (Frontiers in Immunology, 2017)
CANDLE syndrome (Chronic Atypical Neutrophilic Dermatosis with Lipodystrophy and Elevated temperature) is a rare, genetic autoinflammatory disease due to abnormal functioning of the multicatalytic system proteasome – immunoproteasome. Several recessive mutations in different protein subunits of this system, located in one single subunit (monogenic, homozygous or compound heterozygous) or in two different ones (digenic, compound heterozygous) cause variable defects in catalytic activity of the proteasome – immunoproteasome. The final result is a sustained production of type 1 interferons (IFNs) that can be very much increased by banal triggers such as cold, stress or viral infections. Patients start very early in infancy with recurrent or even daily fevers, characteristic skin lesions, wasting and a typical fat loss, all conferring the patients a unique and unmistakable phenotype. So far, no treatment has been effective for the treatment of CANDLE syndrome; the JAK inhibitor baricitinib seems to be partially helpful. In this article, a review in depth all the pathophysiological, clinical and laboratory features of CANDLE syndrome is provided.